1974
DOI: 10.1172/jci107692
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Modulation of Pancreatic Glucagon Secretion in Man

Abstract: A B S T R A C T In order to characterize the influence of the adrenergic system on pancreatic glucagon secretion in man, changes in basal glucagon secretion during infusions of pure alpha and beta adrenergic agonists and their specific antagonists were studied. During infusion of isoproterenol (3 Ag/min), a beta adrenergic agonist, plasma glucagon rose from a mean (±SE) basal level of 104±10 to 171±15 pg/ml, P < 0.0002. Concomitant infusion of propranolol (80 Ag/min), a beta adrenergic antagonist, prevented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…From the present data it might seem that the a-cells of streptozotocin-induced diabetic animals are as resistant to insulin as the normal a-cells. This difference between the two forms of diabetes may be real and a result of the duration of diabetes (3)(4) (19)(20)(21)(22)(23). In the perfused dog pancreas, glucagon secretion is stimulated by low concentrations of epinephrine which in turn is not inhibited by glucose (21).…”
Section: Table Vi)mentioning
confidence: 99%
“…From the present data it might seem that the a-cells of streptozotocin-induced diabetic animals are as resistant to insulin as the normal a-cells. This difference between the two forms of diabetes may be real and a result of the duration of diabetes (3)(4) (19)(20)(21)(22)(23). In the perfused dog pancreas, glucagon secretion is stimulated by low concentrations of epinephrine which in turn is not inhibited by glucose (21).…”
Section: Table Vi)mentioning
confidence: 99%
“…For example, it has been proposed that the effects of a-adrenergic agonism on Acell secretion are (a) stimulatory in ducks (5), rats (6), and man (7, preliminary report); (b) inhibitory in man (8), a study not confirmed by others (9); or (c) not evident in dogs (10). It has also been suggested that ,8-adrenergic agonism either inhibits glucagon secretion in man (7) and ducks (5), or stimulates glucagon in man (8), rats (11), or dogs (10).…”
Section: Introductionmentioning
confidence: 99%
“…Two lines of evidence suggest that the improvted metabolic state of the hypophysectomized, depancreatized dog might be mediated by a deficiency of glucagon secondary to a reduction in corticosteroids and(or) growth hormone (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). First, it has been reported that glucocorticoids increase both the A-cell response to aminogenic stimulation (5,6) and the sensitivity of the liver to glucagon (7,8), suggesting that the adrenocortical insufficiency secondary to pituitary ablation might reduce the secretion and(or) biologic effectiveness of glucagon.…”
Section: Introductionmentioning
confidence: 99%
“…First, it has been reported that glucocorticoids increase both the A-cell response to aminogenic stimulation (5,6) and the sensitivity of the liver to glucagon (7,8), suggesting that the adrenocortical insufficiency secondary to pituitary ablation might reduce the secretion and(or) biologic effectiveness of glucagon. Second, growth hormone itself may enhance glucagon secretion; growth hormone increases the hyperglycemic activity of the pancreatic venous effluent of cats and dogs (9,10), and the secretion of immunoreactive glucagon (11,12), and glucagon levels are reported to be high in acromegalics (13,14). It would not be surprising, therefore, if glucagon levels were reduced by hypophysectomy, and then further reduced by total pancreatectomy, which would leave the gastric fundus as the major site of glucagon secretion (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%